Use of purple corn (Zea mays L.) cob in the formulation of functional teas developed using Flash Profile and CATA methods - Mora-Velit, Jessica (2025)
Purple corn (Zea mays L.) is a superfood native to Peru, highly regarded for its functional properties and commonly used in the preparation of traditional beverages and desserts, such as chicha morada and mazamorra morada. Following processing, the corn cobs remaining as a byproduct retain significant amounts of bioactive compounds with potential for utilization. This study proposes their use as a primary component in the production of teas. To ensure product safety, the moisture content, total ash, and counts of enterobacteria and aflatoxins in the raw materials were first evaluated. Fourteen formulations were developed, varying in the proportions of corn cobs, quince, stevia, cinnamon, and cloves, as well as extraction times (5 and 10 minutes at 100 °C) with hot water. Two rapid sensory evaluation methods using consumer panels were applied sequentially: Flash Profile (FP) and Check-All-That-Apply (CATA), External preference mapping was then conducted, and the most acceptable teas were subjected to instrumental characterization. The FP methodology generated 400 sensory descriptors, classified semantically, from which 12 key descriptors were selected for the CATA test: sweet, stevia flavor, quince flavor, fruity flavor, fruity smell, astringent, bitter, cinnamon smell, reddish color, acid, purple and “Chicha morada” flavor. The confidence ellipses in the FP Multiple Factor Analysis (MFA) space allowed to identify six groups of formulations for the CATA test. This test revealed that the characteristics that improve consumer acceptability are: “Chicha morada” flavor, fruity flavor, sweet and fruity smell. The External Preference Mapping allowed to determine the formulations, with 90% preference among consumers, despite not being the ones with the highest concentrations of total polyphenols, antioxidant activity and monomeric anthocyanins. In conclusion, the sensory methodologies applied in this study help to elucidate the sensory characteristics that influence consumer acceptability, representing valuable tools for the development of new functional products from purple corn.